Repositioning the Teacher for Sustainable African Education Beyond Covid 19 Pandemic - Egwuasi, Princewill Ikechukwu; Nwamara, Ezinne Nkeiru; Okon, Nsikak Mkpong; Monday, Janet Sunday; Nwakwesiri, Chinwe Francisca (EDUPEDIA Publisher, 2022)
The teacher in the education project is at the centre of the wheel, without which the efforts in the success story can never be sustained. This paper therefore examines the re-positioning of the teacher for sustainable education in post-COVID 19 era in Nigeria and Africa in general. To actualize this, the evaluation theory became the theoretical foundation; with a look at the African education retrospectively. A strong correlation was established between the “New Normal” and the teacher. In the end, the paper averred, among other things, that the teachers should become digital specialists, while education providers at all levels should prioritise remote learning process, revamp digital skills and education curriculum and enhance audio-visual learning. Among other recommendations were that the government should ensure inclusion of online teaching, provide the needed facilities, while the teachers themselves must be ready to move into the fast lanes of technology and protective teaching.